Paternal low protein diet affects adult offspring cardiovascular and metabolic function in mice - Watkins, Adam J.; Sinclair, Kevin D. (American Physiological Society, 2014)
Whilst the association between maternal periconceptional diet and adult offspring health is well characterised, our understanding of the impact of paternal nutrition at the time of conception on offspring phenotype remains poorly defined. Therefore, we determined the effect of a paternal preconception low protein diet (LPD) on adult offspring cardiovascular and metabolic health in mice. Male C57BL/6 mice were fed either normal protein diet (18% casein; NPD) or LPD (9% casein) for 7 weeks prior to mating. At birth, a reduced male:female ratio (P=0.03) and increased male offspring weight (P=0.009) were observed in litters from LPD compared to NPD stud males with no differences in mean litter size. LPD offspring were heavier than NPD offspring at 2 and 3 weeks of age (P<0.02). However, no subsequent differences in body weight were observed. Adult male offspring derived from LPD studs developed relative hypotension (decreased by 9.2 mmHg) and elevated heart rate (P<0.05), whilst both male and female offspring displayed vascular dysfunction and impaired glucose tolerance relative to NPD offspring. At cull (24 weeks), LPD males had elevated adiposity (P=0.04), reduced heart:body weight ratio (P=0.04) and elevated circulating TNF-α levels (P=0.015) when compared to NPD males. Transcript expression in offspring heart and liver tissue was reduced for genes involved in calcium signalling (Adcy, Plcb, Prkcb) and metabolism (Fto) in LPD offspring (P<0.03). These novel data reveal the impact of sub-optimal paternal nutrition on adult offspring cardiovascular and metabolic homeostasis, and provide some insight into the underlying regulatory mechanisms.